Contribuições da aprendizagem dialógica para a educação ambiental e suas possíveis convergências - Sant'ana, Flávia Maria Gonçalves de (2011)
The Brazilian environmental education is multifaceted, consisting of various politicalpedagogical conceptions. According to this background, the environmental educator chooses what ideas are best suited to his or her ideals of society and environment. This research is based in ideals of an egalitarian society, in which the social relations are marked by respect to all forms of life and by equal rights and opportunities for all the people. In this sense, the research had as it purpose to offer more possibilities to actions in the area of environmental education to suggest the concept of dialogic learning in order to increase the use of critical environmental education. At last, it discusses theoretically the possible contributions of dialogic learning for environmental education using the methodology of bibliographical research. The study included surveys of the main references in the Brazilian environmental education and learning dialogic and analyzed them in order to present their similarities and potential contributions of dialogic learning for environmental education. At the end of the analysis, we conclude that many of the assumptions of the dialogic learning are present, even though they are scattered, in different conceptions of environmental education, which is based on the principles of dialogic learning and may have its horizon expanded and make their criticality and the search for social transformation and environmental preservation stronger, suggesting concrete directions so it can be socially built.